Strategies to Enhance the Teaching Competence of University Teachers in English Major - Xiang, Yafang (International Journal of Emerging Technologies in Learning (iJET), 2021)
This paper aims to find strategies to improve the teaching ability of college teachers in English major, which is affected by various factors. Firstly, the teaching ability deficiencies of college teachers in English major were analyzed, and the connotations of this ability were summarized. On this basis, a novel measurement system was established for the teaching ability of college teachers in English major. Then, analytical hierarchy process (AHP) was combined with Shannon’s information theory into an improved model to measure the said teaching ability. In addition, several strategies were presented to improve teaching ability of college teachers in English major. The research results provide a good guide for the teaching reform in English major.